2017
DOI: 10.1016/j.jgr.2015.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside Rg1 suppresses early stage of adipocyte development via activation of C/EBP homologous protein-10 in 3T3-L1 and attenuates fat accumulation in high fat diet-induced obese zebrafish

Abstract: BackgroundGinsenoside Rg1 is a class of steroid glycoside and triterpene saponin in Panax ginseng. Many studies suggest that Rg1 suppresses adipocyte differentiation in 3T3-L1. However, the detail molecular mechanism of Rg1 on adipogenesis in 3T3-L1 is still not fully understood.Methods3T3-L1 preadipocyte was used to evaluate the effect of Rg1 on adipocyte development in the differentiation in a stage-dependent manner in vitro. Oil Red O staining and Nile red staining were conducted to measure intracellular li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 46 publications
1
25
0
Order By: Relevance
“…Ginseng saponins can be subdivided based on structure into Rb1, Rb2, Rc, Rd, Re, and Rl [36, 37]. Panax ginseng C. A. Mey can reduce body weight [61], attenuate fat accumulation [62], suppress lipid accumulation and reactive oxygen species (ROS) production [63], and improve insulin resistance [64]. Li et al [65] found that administration of ginseng (0.5 g/kg diet) to HFD-induced obese mice for 15 weeks significantly decreased body fat mass gain, improved glucose tolerance and insulin sensitivity, and prevented hypertension.…”
Section: Resultsmentioning
confidence: 99%
“…Ginseng saponins can be subdivided based on structure into Rb1, Rb2, Rc, Rd, Re, and Rl [36, 37]. Panax ginseng C. A. Mey can reduce body weight [61], attenuate fat accumulation [62], suppress lipid accumulation and reactive oxygen species (ROS) production [63], and improve insulin resistance [64]. Li et al [65] found that administration of ginseng (0.5 g/kg diet) to HFD-induced obese mice for 15 weeks significantly decreased body fat mass gain, improved glucose tolerance and insulin sensitivity, and prevented hypertension.…”
Section: Resultsmentioning
confidence: 99%
“…A number of factors including C/EBPα, PPARγ, and aP2 are important for the development of adipocyte [34]. The beneficial effect of dietary extracts derived from fruits or vegetables have been showed on controlling C/EBPα, PPARγ, and aP2 in vitro and in vivo [35,36,37]. Inafuku and colleagues [38] provided a clue that Cirsium Brevicaule A.…”
Section: Discussionmentioning
confidence: 99%
“…SST consists of seven medicinal herbs: Bupleuri Radix, Scutellariae Radix, Ginseng Radix, Pinelliae Tuber, Zingiberis Rhizoma Crudus, Zizyphi Fructus, and Glycyrrhizae Radix et Rhizoma. Among these components, baicalin [ 26 , 27 ] and baicalein [ 28 ] from Scutellariae Radix and ginsenoside Rg1 from Ginseng Radix Alba [ 29 ] are well known for antiadipogenic effects. Although a previous study indicated that SST suppresses epididymal fat weight and altered serum lipid profile in high fat-fed rats [ 30 ], the regulatory mechanisms responsible for the antiobesity effect of SST have not been elucidated.…”
Section: Discussionmentioning
confidence: 99%